Is Shortwave Diathermy Effective on Mortality of Protoscolices? - Eslamirad, Zahra; Hajihossein, Reza; Soleimani, Homa (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: Aprevious study confirmed the effect of microwaves on protoscolices in vitro. In the current study, the effect of shortwave diathermy (SWD) on the protoscolices of hydatid cysts was investigated. MATERIALS AN DMETHODS: The hydatid cyst was collected from the slaughterhouse and its contents were drained sterilized. SWD therapy was done in continuous mode. The experiment was conducted based on electrode area, power of device, and exposure time.GraphPad and SPSS software was used for data analysis. RESULTS: The study results showed that the two main factors of time exposure and power of the machine could significantly effective in the mortality rate of protoscolices compared to control (p < 0.0001). Scolicidal activity of SWD in 450 w was 4.5%, 8.3%, and 10%, respectively, after 2, 5, and 10 min with ΔT = 0.5°C, 14°C, and 16°C. The results of the study showed that the simultaneous effect of two factors of power and time exposure increased significantly death rate of protoscolices compared to control (p < 0.05). CONCLUSION: Since the application of SWD has limited risks, ease of use, and relative low cost and it can induce hyperthermia in depth of tissues, continuous SWD can be used as a tool for preoperative in surgery. However, it is likely that scolicidal activity can be observed by changing the device mode in pulse short wave at a lower temperature and also the possible side effects need further investigation in vivo.